The Role of Ubiquitination in NF-κB Signaling during Virus Infection - Kun Song (Viruses, 2021)
The nuclear factor κB (NF-κB) family are the master transcription factors that control cell proliferation, apoptosis, the expression of interferons and proinflammatory factors, and viral infection. During viral infection, host innate immune system senses viral products, such as viral nucleic acids, to activate innate defense pathways, including the NF-κB signaling axis, thereby inhibiting viral infection. In these NF-κB signaling pathways, diverse types of ubiquitination have been shown to participate in different steps of the signal cascades. Recent advances find that viruses also modulate the ubiquitination in NF-κB signaling pathways to activate viral gene expression or inhibit host NF-κB activation and inflammation, thereby facilitating viral infection. Understanding the role of ubiquitination in NF-κB signaling during viral infection will advance our knowledge of regulatory mechanisms of NF-κB signaling and pave the avenue for potential antiviral therapeutics. Thus, here we systematically review the ubiquitination in NF-κB signaling, delineate how viruses modulate the NF-κB signaling via ubiquitination and discuss the potential future directions.